Implementation of Literacy Activities in Establishing Character of Students - Carolina Sasabone; Yoesoep Edhie Rachmad; Faisal Kemal; Endang Fatmawati; Muh. Safar (Journal on Education, 2023)
This research focuses on literacy activities carried out at the school and the character building of school students with their literacy programs. Related to this research, the authors used mixed methods research, in which this study used two approaches, namely qualitative and quantitative. In this study, the naturalistic method will be used, where this method will be carried out in natural conditions (natural settings) by making thorough observations on a certain background without changing it one bit. During this research process, there will be no conditions that are altered or engineered in the slightest; everything is natural and occurs naturally in the field. . It was the director of education and the founder of the school who were the originators of the literacy programs that have been running so far in schools. The truth is that children at school are not far from what is called literacy; they will always meet literacy. Literacy in their environment greatly influences the child's mindset and personality; therefore, the school-encouraged literacy program is one of the leading programs both in increasing literacy levels, which basically cover 4 language skills (listening, speaking, reading, and writing), as well as in forming superior character, personality, attitude, and behavior as well.